O LUTO COMO DESCONSTRUÇÃO DA IDENTIDADE DO SUJEITO EM JUDITH BUTLER (Razão e Fé, 2022)
The aim of this article is to demonstrate how the deconstruction of the subject's identity occurs in the mourning process from Butler's philosophy. To do so, two arguments are presented. The first refers to the importance of mourning for the subject who, after a loss, needs to reorganize and rebuild his life in the face of the fact that has occurred. The second indicates intersubjectivity as a fundamental point for understanding the processes of mourning to the extent that it is the undoing of human relations that has a decisive impact on the deconstitution of the identity of the living, that is, the one who lives and suffers.